Effectiveness of Emotion-Focused Therapy on Suicidal Ideation and Distress Tolerance in Adolescents with Borderline Personality Disorder Symptoms - Nikkhah Siruei, Zahra; baloochan, Mansoureh; fazeli Mehrabadi, Alireza (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to investigate the effectiveness of Emotion-Focused Therapy (EFT) on suicidal ideation and distress tolerance in adolescents with symptoms of borderline personality disorder (BPD).Methods and Materials: This quasi-experimental study employed a pretest–posttest design with a control group. The statistical population included all adolescents with BPD symptoms who referred to Sepidaran Ravan Counseling Center and Shorooe Zendegi Clinic in Tehran in 2024 due to interpersonal problems. Using multi-stage sampling (convenience in the first stage and purposive in the second), 30 eligible adolescents were selected. Participants were randomly assigned to the experimental and control groups (15 each). The experimental group received 12 ninety-minute EFT sessions twice weekly based on Greenberg’s (1980) protocol, while the control group was placed on a waiting list. Research instruments included the Borderline Personality Assessment Questionnaire (STB), Beck Suicidal Ideation Questionnaire (1961), and the Distress Tolerance Scale (DTS-15; Simons & Gaher, 2005). Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA) with SPSS-24.Findings: After controlling for pretest scores, ANCOVA results indicated a significant reduction in suicidal ideation in the experimental group compared to the control group (F = 15.11, p < 0.01, η² = 0.36), with EFT accounting for 36% of the variance in suicidal ideation. Similarly, a significant improvement in distress tolerance was observed in the experimental group compared to the control group (F = 5.86, p < 0.01, η² = 0.249), with EFT explaining 24.9% of the variance in distress tolerance.Conclusion: EFT effectively reduced suicidal ideation and enhanced distress tolerance in adolescents with BPD symptoms. By targeting maladaptive emotional responses and fostering adaptive emotional processing, EFT can be considered a valuable therapeutic option for high-risk adolescents to improve emotional resilience and reduce self-destructive tendencies.